PENINGKATAN KETERAMPILAN MENULIS ANEKDOT MENGGUNAKAN STRATEGI GENIUS LEARNING - Suryaningsih, Sri (sarasvati, 2021)
The purpose of this study, is to improve the anecdote writing skills of class X OTKP students of SMK Negeri 1 Telen in the academic year 2020/2021 by implementing a genius learning strategy. Classroom action research methods. Classroom action research design begins with planning, action, observe and reflect. Learning with a genius learning strategy can improve the results of anecdotal writing skills. This can be seen from the average score of writing anecdotes before being given action was 64.53, after being given the action at the end of the first cycle the average score became 75.58. The average score of writing anecdotes at the end of cycle II was 85.00. This indicates an increase of 20.47 points. Overall, at the end of the second cycle, all aspects and criteria for writing anecdotes had a significant increase. From the results of the above research, it is evident that the use of the genius learning strategy is considered successful and can improve the anecdote writing skills of the students of class X OTKP SMK Negeri 1 Telen.